Feminine subjectivities and aspirational learner identities: Asian–Australian young women navigating possible selves in the first year of university. Issue 7 (3rd October 2021) - Stahl, Garth; McDonald, Sarah; Loeser, Cassandra
ABSTRACT: In educational research, girls are frequently depicted as success stories, able to effortlessly navigate academic excellence as empowered females. However, these depictions lack nuance and often fail to capture the complexity of young women's experiences as they shift from compulsory schooling into higher education. Using a methodology of semi-structured interviews and focus groups occurring at three points over the course of the first year of university, we explore the experiences of two young women, Joy and Naomi, both from Asian backgrounds. Focusing on possibilities, positioning and performances of femininities in relation to academic experiences, the article considers how their time in an Australian university informs their aspirations and subjectivities where the university is theorised as a site for the (re)making of identities. We draw on the model of possible selves which deepens our understanding of identities in formation allowing us to nuance processes of 'change' and 'transformation.'